Do consumer‐mediated negative effects on plant establishment outweigh the positive effects of a nurse plant?. Issue 7 (6th March 2018) - Fujita, Tomohiro; Yamashina, Chisato
Abstract: Many studies demonstrated the importance of facilitative effect by nurse plant on seedling establishment. Few studies evaluated the negative effects of consumers on plant establishment under nurse plants by dealing with them during multiple demographic processes. We investigated the balance between the facilitative effect and negative effects of consumers during multiple demographic processes in Malawi in southeastern Africa. We chose Ficus natalensis as a nurse plant and compared it with three other microsites in tropical woodlands: Brachystegia floribunda (a dominant woodland species), Uapaca kirkiana (a woodland species), and a treeless site. We quantified the seed rain, postdispersal seed predation, germination, and seedling survival of Syzygium guineense ssp. afromontanum (a common forest species). Within each microsite, we quantified the overall probability of recruitment. We also measured seedling abundance of S. guineense ssp. afromontanum . We found that Ficus natalensis exerted both positive and negative impacts on the establishment of S. guineense ssp. afromontanum . Ficus natalensis facilitated seed deposition, seed germination, and seedling survival. On the other hand, seed removal at postdispersal stage was highest under F. natalensis . Interestingly, B. floribunda also had positive effects on germination and seedling survival, but not on seed deposition. When we excluded the seed arrival stage from our estimation of the recruitment probability, the highest value was found under B. floribunda, not under F. natalensis . When we included the seed arrival stage, however, the order of recruitment probability between F. natalensis and B. floribunda was reversed. The probability was one order of magnitude higher under F. natalensis than under B. floribunda . Our estimation of the probability which included the seed arrival stage was consistent with natural patterns of S. guineense ssp. afromontanum establishment. Despite the presence of opposite effects, the net effects of F. natalensis on S. guineense ssp. afromontanum recruitment in tropical woodlands can be positive. Abstract : Through experiment, we found that nurse plant exerted opposing effects on establishment of beneficiary species by facilitating seed deposition, seed germination, and seedling survival and by simultaneously increasing the risk of seed predation. Based on above experiments, we estimated the transition probability. According to the estimation, we found the net effect of nurse plant on the establishment can be facilitative.